Pengaruh Budaya Perusahaan, Dewan Direksi, dan Kinerja Karyawan terhadap Good Corporate Governance dengan Audit Internal Sebagai Variabel Intervening pada Perusahaan Sektor Perbankan yang Terdaftar di BEI - Tengku Hasan Basri; Lukertina Lukertina; Supardi Supardi; Audita Audita (Politeknik Ganesha Medan, 2022)
Good Corporate Governance is the most important thing for companies, especially leaders to supervise or monitor all company operational activities. Banking is required to prioritize the implementation of optimal governance or Good Corporate Governance (GCG) during this Covid-19 pandemic era so that corporation does not cause new impacts during the pandemic. An internal audit in one of factor that impact of organizational culture on the internal control environment and organizational risk, this is because a negative organizational culture will have a negative impact on the company and the implementation of corporate governance. Various inputs should be suggested to an organization in order to be able to create a healthy organizational culture. The research carried out by the researchers has the aim of analyzing the determinants of good corporate governance in the banking sector that are included in the IDX list. Purposive sampling was used as a data collection method in this study. Data was obtained by distributing questionnaires/questionnaires to 10 banks located in Central Jakarta. Data were analyzed by SEM-PLS with bootstrapping method using smartPLS 3.0. software package. The results showed that corporate culture, board of directors, and employee performance had a significant effect on good corporate governance with internal audit as a intervening variable either partially or simultaneously.